The Influence Of Organizational Culture And Quality Of Work Life On Motivation And Its Implications On Employee Loyalty - Maulana Saputra, Mochammad Sahrul; Hermawati, Adya; Soedjono, Soedjono (Bulletin of Management and Business, 2024)
This research aims to identify the influence of organizational culture and Quality of Work Life on employee motivation, as well as its implications for employee loyalty. A healthy organizational culture and good Quality of Work Life can act as crucial factors in building high motivation among employees, which in turn can form strong loyalty. This research method uses a quantitative approach by distributing questionnaires to 67 respondents, such as regression and path analysis, is used to evaluate relationships between variables. The research results show that a better work culture and quality of work life can increase motivation, a better work culture and quality of work life can increase loyalty, better motivation can increase loyalty, work motivation can be a mediating variable between work culture and loyalty, and quality of work life on loyalty.